A prospective study of cognitive deficits in first episode psychosis, and the response thereof to treatment with Flupenthixol Decanoate - Schoeman, Renata (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD (Psychiatry))--University of Stellenbosch, 2011.